Organophosphorus pesticide residue levels in homes located near orchards. Issue 12 (2nd December 2018) - Butler-Dawson, Jaime; Galvin, Kit; Thorne, Peter S.; Rohlman, Diane S.
Abstract: Organophosphorus pesticides (OPs) are commonly applied to agricultural crops. Families living in these communities may have higher exposure to OPs due to take home exposures and close proximity to agricultural fields. The objectives of this study were to measure OP concentrations in home carpet dust in agricultural and non-agricultural households and examine factors that may impact OP concentrations such as occupation, housing characteristics, and resident behaviors. Agricultural households had at least one parent who worked in agriculture during the previous 5 years. Carpet dust samples were collected at two time points from 278 households in an agricultural community located in the Pacific Northwest from 2008–2011. Samples were analyzed for four types of OPs: azinphos-methyl, phosmet, malathion, and chlorpyrifos. Overall, OP detection frequencies and concentrations were higher in agricultural households compared to non-agricultural households. Factors associated with higher OP concentrations in home carpet dust were identified and included: (1) homes with two or more agricultural workers living in the home, (2) homes located in close proximity to an agricultural field or orchard, (3) having an entry floor mat, and (4) frequently vacuuming the house. Having air conditioning in the home had a protective effect with OP concentrations. While the use of these four OPs is restricted or limited for residential use in the United States, results show that they were still found in the indoor environment. The understanding of the impact of agricultural work and other factors that elevate levels of OPs in the home is crucial to mitigating pesticide exposure in agricultural communities.